2016
DOI: 10.1177/2158244016634409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cadmium Polluted Groundwater on Human Health

Abstract: A number of serious studies have been conducted to decipher relationships between geological environment, potable/ drinking water, and diseases as they were considered to have triggered suffering due to diseases among people. Chronic anemia can be caused by prolonged exposure to drinking water contaminated with cadmium (Cd). Under such circumstances, accumulation of Cd is manifested in the kidney, resulting in cancer and cardiovascular diseases. The aim of this study is to present the impact of Cd-contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Interview based data collection is one of the easiest ways through which most precise and pertinent questions may be developed to focus on any problem to be investigated in any study. Questionnaire survey has been deemed as the most common technique in this regard (Burke, et al, 2016, Miandad, et al, 2015a. The structured and open ended questionnaire administered to patients in the present study contained queries regarding relevant risk factors with reference to TB in the perspective of geodemographic/socio-ecological conditions of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Interview based data collection is one of the easiest ways through which most precise and pertinent questions may be developed to focus on any problem to be investigated in any study. Questionnaire survey has been deemed as the most common technique in this regard (Burke, et al, 2016, Miandad, et al, 2015a. The structured and open ended questionnaire administered to patients in the present study contained queries regarding relevant risk factors with reference to TB in the perspective of geodemographic/socio-ecological conditions of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Cadmium (Cd), as a highly toxic heavy metal, can be released into water by the corrosion of galvanized pipes, erosion of natural deposits, metal refineries discharge and waste batteries and paint runoff. Exposure to cadmium causes acute and chronic health issues such as hypercalciuria, renal failure, kidney stones, cardiovascular diseases, anemia and lung and prostate cancer due to high exposure [88,89].…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
“…Some farmers use composts (from inorganic sources), fertilizers and plant nutrients in relatively large amounts that are rich in some metals and this might explain some of the higher value of metals in the mint. Besides, contamination from industrial activities nearby mint farms might also expected [1,4,9].…”
Section: Microwave-assisted Digestionmentioning
confidence: 99%
“…The consumption of mint that contaminated with high amount of heavy metals has an adverse effect on the human health. For instance, an acute cadmium dose of 10-30 mg/kg/day was reported to trigger impacts like excessive salivation, diarrhea and vomiting [4]. The cadmium dose of 25 mg per kg body weight had been reported that it may lead to death [5].…”
Section: Introductionmentioning
confidence: 99%